The Determinant of Student Consumptive Behavior: The Role of Financial Literacy, Self-Control, and Lifestyle at Universitas Muhammadiyah Sumatera Utara - Soebandono, Wendy; Pasaribu, Fajar; Khair Pasaribu, Hazmanan; Pratama, Nugraha (AIBPM Publisher, 2025)
This research explores the relationship between financial literacy, self-control, and lifestyle in shaping the consumptive behavior of students enrolled in the 2018 Financial Concentration of the Management Study Program at UMSU. Recognizing the rising concern over impulsive spending among university students, the study adopts a quantitative associative approach to examine how these three factors contribute to such behavior. A total of 54 students participated as respondents, and the data collected were analyzed using SPSS version 25. The analysis employed various statistical tests, including multiple linear regression, normality and heteroscedasticity testing, multicollinearity checks, t-tests, F-tests, and the coefficient of determination, to ensure accuracy and reliability. The findings reveal that financial literacy, self-control, and lifestyle exert a notable influence on individuals' tendencies toward consumptive behavior. Moreover, when analyzed together, these variables also demonstrate a meaningful and statistically significant combined influence, indicating that a comprehensive approach addressing all three elements is crucial for understanding and potentially reducing consumptive tendencies among students